Partisipasi Masyarakat dalam Penataan Pemukiman Kumuh di Kawasan Perkotaan: Study Kasus Kegiatan PLP2K-BK di Kota Medan dan Kota Payakumbuh - Noegroho, Noegi (ComTech: Computer, Mathematics and Engineering Applications, 2012)
In any city development, it is important to urge people to be involved in so that the development can be valued as much as possible. Model of involvement is certainly diverse, such as 'one-way involvement' in which people tend to just listen, and 'two-way involvement' where the people to participate to make a decision. This paper observes how the public participated in the arrangement of slum area undertaken by the Government. Although there has been community involvement in this activity, there are still any limitations.